Perceptions of students regarding innovative approaches introduced in nutrition and metabolism module at Shifa college of medicine - Iqra Anwar; Sumreena Mansoor; Saima Saeed; Sajid Rashid (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the perceptions of 2nd year medical students regarding certain approaches introduced in the course of Nutrition and Metabolism module. Method: The descriptive study was conducted at the Shifa College of Medicine, Islamabad, Pakistan,in December 2020, and comprised all 2nd year medical students who completed the Nutrition and Metabolism module in which new components had been added, including introduction to community nutrition, school visits, Islamic perspective of nutrition, journal club and e-posters.Data was collected usinga questionnaire based on the modified Dundee Ready Education Environment Measure, and had 5 categories with a total of 25 questions that were scored on a 5-point Likert scale. Data was analysed using SPSS 22. Results: Of the 100students, 65(65%)were females and 35(35%)were males. The overall mean age was 20.5 ± 0.5 years. The total mean score was 74.68±2.53. mean score for student’s perception of learning was 38.17±0.17, student’s perception of teachers 9.27±0.18, student’s academic self-perceptions 12.1±0.11, student’s perceptions of atmosphere 9.03±0.03 and student’s social self-perceptions 6.11± 0.01. Conclusion: The perceptions medical students about innovations were positive, showing an encouraging attitude in terms of learning approach and outcome. Key Words: Educational environment, Problem-based learning, DREEM, Innovations, Shifa college.